Clinical record looked at from the current Chilean legislation - Godoy Olave, Jorge; Barraza Mesquida, Jaime (Acta Bioethica, 2018)
The history or clinical record has served as an element of registration of health activities since the beginning of the health professions, granting him other utilities and valuations according to their objective, as a teaching value, in research, judicial, among others. Given the different interpretations of the norms in force in Chile, it has had to legislate in its use, membership, content and other aspects of the clinical file, clarifying some situations, but restricting their access in other aspects. Given the different laws and regulations associated with its use, it became necessary to produce a document that collects its most important aspects. There are still aspects associated with customs, beliefs, specialties in health, among others, that have not been addressed by the Laws, in addition to the teaching work of this instrument.